The little mermaid ebook - Andersen, Hans Christian (Prospekt LLC, 2011)
"The Little Mermaid" is a fairy tale by the Danish poet and author Hans Christian Andersen about a young mermaid willing to give up her life in the sea and her identity as a mermaid to gain a human soul and the love of a human prince.